2002
DOI: 10.1152/ajpcell.00318.2001
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II AT2 receptor inhibits smooth muscle cell migration via fibronectin cell production and binding

Abstract: To explore the vascular function of the angiotensin II (ANG II) AT(2) receptor subtype (AT(2)R), we generated a vascular smooth muscle cell (SMC) line expressing the AT(2)R (SMC-vAT(2)). The involvement of AT(2)R in the motility response of SMCs was examined in SMC-vAT(2) cells and their controls (SMC-v) cultured on either laminin or fibronectin matrix proteins with the agarose drop technique. All experiments were conducted in the presence of a saturating concentration of losartan to inactivate the AT(1)R subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…This occurred despite significant increase in fibronectin, which we demonstrated is modulated by AT 2 receptors. 18 In support of our findings, Chassagne et al 32 demonstrated that AT 2 receptor activation inhibited VSMC migration through fibronectin secretion and subsequent VSMC attachment. It is therefore possible that ␣ 5 subunit expression, which can mediate cell attachment to fibronectin, is associated with a nonmigratory VSMC phenotype.…”
Section: Discussionsupporting
confidence: 88%
“…This occurred despite significant increase in fibronectin, which we demonstrated is modulated by AT 2 receptors. 18 In support of our findings, Chassagne et al 32 demonstrated that AT 2 receptor activation inhibited VSMC migration through fibronectin secretion and subsequent VSMC attachment. It is therefore possible that ␣ 5 subunit expression, which can mediate cell attachment to fibronectin, is associated with a nonmigratory VSMC phenotype.…”
Section: Discussionsupporting
confidence: 88%
“…Another possible atheroprotective mechanism of AT 1 R blockade could be that ''free'' AngII could bind to the AT 2 R. Stimulation of the AT 2 R has been shown to inhibit neo-intimal formation (Janiak et al 1992), decrease smooth muscle cell proliferation (Nakajima et al 1995) and migration (Chassagne et al 2002), and inhibit fibroblast proliferation (Tsuzuki et al 1996). Moreover, AngII can be converted to Ang (1-7) by ACE2 (Boehm and Nabel 2002).…”
Section: Discussionmentioning
confidence: 99%
“…88 Ang-II may also inhibit SMC migration through the AT2 receptor by increasing cellular FN synthesis and associated cell binding. 89 IGF-1, a small polypeptide with structural homology to proinsulin, is produced by many cell types and acts as an autocrine/paracrine growth factor. It has been postulated to play a role in SMC growth in the bladder, uterus, and vasculature.…”
Section: Molecular Regulation Of Contractile Smooth Muscle Cell Phenomentioning
confidence: 99%